2015
DOI: 10.1002/j.0022-0337.2015.79.10.tb06012.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Dental Students’ Awareness of Health Care Disparities and Desire to Serve Vulnerable Populations Through Service‐Learning

Abstract: Service-learning in dental education helps students integrate knowledge with practice in an underserved community setting. The aim of this study was to explore how a service-learning experience affected a small group of dental students' beliefs about cultural competence, professionalism, career development, desire to practice in a community service setting, and perceptions about access and disparities issues. Prior to beginning their irst year of dental school, ive irst-year dental students at one U.S. dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 18 publications
1
59
0
Order By: Relevance
“…Students can benefit from social justice education by gaining greater insight into the experiences of people they encounter in their professional careers. This holistic understanding then supports the provision of socially just and empathetic dental care …”
Section: Introductionmentioning
confidence: 74%
“…Students can benefit from social justice education by gaining greater insight into the experiences of people they encounter in their professional careers. This holistic understanding then supports the provision of socially just and empathetic dental care …”
Section: Introductionmentioning
confidence: 74%
“…A previous study found value in integrating service‐learning into dental education, developing dental students’ cultural competence, and raising their willingness to treat underserved populations 13 . That study pointed to the urgent need to integrate some form of service‐learning into dental faculty development programs.…”
Section: Discussionmentioning
confidence: 93%
“…Many kinds of learning tools, approaches, and course designs were assessed. The most frequently assessed learning tool was reflection, whether used alone or with other modalities 6 , 25 32 . Reflection is a tool that helps students to think critically about course content and their experiences in the community 33 .…”
Section: Resultsmentioning
confidence: 99%